Physiological Responses to Abiotic and Biotic Stress in Forest Trees - Polle, Andrea; Rennenberg, Heinz (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
As sessile organisms, plants have to cope with a multitude of natural and anthropogenic forms of stress in their environment. Due to their longevity, this is of particular significance for trees. As a consequence, trees develop an orchestra of resilience and resistance mechanisms to biotic and abiotic stresses in order to support their growth and development in a constantly changing atmospheric and pedospheric environment. The objective of this Special Issue of Forests is to summarize state-of-art knowledge and report the current progress on the processes that determine the resilience and resistance of trees from different zonobiomes as well as all forms of biotic and abiotic stress from the molecular to the whole tree level.
English
Keywords: pure stands; n/a; ion relation; Heterobasidion annosum; salicylic acid; antioxidant enzymes; antioxidant activity; Luquasorb; intrinsic water-use efficiency; Greece; Pinus koraiensis Sieb. et Zucc; ion homeostasis; photosynthesis; Pinus massoniana; Stockosorb; water relations; Norway spruce; rubber tree; hydrophilic polymers; drought stress; ion relationships; Carpinus betulus; tree rings; N nutrition; disturbance; Populus simonii Carr. (poplar); infection; subcellular localization; basal area increment; mixed stands; photosynthetic responses; Aleppo pine; water potential; elevation gradient; living cell; physiological response; antioxidant enzyme activity; ion contents; signal network; expression; soil N; GA-signaling pathway; differentially expressed genes; Ca2+ signal; climate; ecophysiology; Robinia pseudoacacia L; Heterobasidion parviporum; mid-term; plant tolerance; canopy conductance; DELLA; tapping panel dryness; osmotic adjustment substances; abiotic stress; wood formation; malondialdehyde; salinity treatments; organic osmolytes; bamboo forest